Code Switching and Code Mixing in the Conversations of the Characters in the Film Uang Panai 2 - Muhammad Rizal Hardin; Saifullah; Kamal Podding; Nuraini Kasman (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to describe the forms of code switching and code mixing found in conversations between the characters. This research employs a qualitative descriptive approach, which is used to identify and describe particular events or phenomena. The data collection techniques applied in this study were repeated observation and note-taking of the findings, while the data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The source of the data in this study was the film Uang Panai 2, which is available on the Netflix application. Based on the results of the study, 41 data items relevant to this research were identified. These data were divided into 23 items in the code-switching category, consisting of 7 instances of internal code switching, 5 instances of external code switching, 5 instances of situational code switching, and 5 instances of metaphorical code switching. Meanwhile, 19 data items were categorized as code mixing, consisting of 7 instances of internal code mixing, 6 instances of external code mixing, and 6 instances of hybrid code mixing. Based on these findings, it can be concluded that the use of code switching and code mixing in the film Uang Panai 2 demonstrates a strong ability to combine various languages in order to convey the message of the film, including the Bugis language, Makassarese, English, and Korean. The mixing of languages also becomes an interesting element in the film, allowing the characters to deliver messages according to the context of the conversation and to adapt to their interlocutors through the use of code switching and code mixing as a key to communication.